Hack Proofing Your Network, Second Edition - Ahmad, David R. Mirza (Syngress Publishing, Inc., 2011)
A new edition the most popular Hack Proofing book around! IT professionals who want to run secure networks, or build secure software, need to know about the methods of hackers. The second edition of the best seller Hack Proofing Your Network, teaches about those topics, including: · The Politics, Laws of Security, Classes of Attack, Methodology, Diffing, Decrypting, Brute Force, Unexpected Input, Buffer Overrun, Sniffing, Session Hijacking, Spoofing, Server Holes, Client Holes, Trojans and Viruses, Reporting Security Problems, Choosing Secure Systems